Design of the Multi-Bioactive Graphene-Oxide/Gelatin/Alginate Scaffolds as Dual ECM-Mimetic and Specific Wound Healing Phase-Target Therapeutic Concept for Advanced Wound Healing - Marko Demenj; Martina Žabčić; Marija Vukomanović; Tatjana Ilić-Tomić; Dušan Milivojević; Simonida Tomić; Dubravka Živanović; Marija M. Babić Radić (Pharmaceutics)
Objectives: To develop and evaluate graphene oxide/gelatin/alginate scaffolds for advanced wound therapy capable of mimicking the native extracellular matrix (ECM) and bio-stimulating all specific phases of the wound healing process, from inflammation and proliferation to the remodeling of damaged skin tissue in three dimensions. Methods: The scaffolds were engineered as interpenetrating polymeric networks by the crosslinking reaction of gelatin in the presence of alginate and characterized by structural, morphological, mechanical, swelling properties, porosity, adhesion to the skin tissue, wettability, and in vitro simultaneous release of the active agents. Biocompatibility of the scaffolds were evaluated in vitro by MTT test on fibroblasts (MRC5 cells) and in vivo using Caenorhabditis elegans assay. Results: The scaffolds exhibited a highly porous interconnected morphology with adjustable porosity (93–96%) and mechanical strength (1.10–2.90 MPa), hydrophilic nature with high capacity to absorb physiological fluids, and stable adhesion to the skin tissue. The obtained results of MRC5 cell viability indicate that the scaffolds are safe for biomedical applications. No mortality was detected among the Caenorhabditis elegans throughout the incubation period, indicating that the scaffolds are not toxic. The results of in vitro release study of allantoin, quercetin, and caffeic acid confirm the scaffolds’ significant potential for simultaneous release. Conclusion: The graphene oxide/gelatin/alginate scaffolds are promising candidates for non-invasive, dual ECM-mimetic, and multi-target wound therapy, offering an innovative strategy to address the complexities of wound healing process.